Influence of financial resources and human resources on business performance of commercial enterprises - Hung, Tran Huy; Dung, Do Thi Van; Phuong, Mai Quynh; Long, Vu Le; Hien, Do Cam (Edelweiss Applied Science and Technology, 2025)
Large-scale commercial activities in economic centers like Hanoi contribute to tax collection, attract capital (investment in stores, warehouses, and digital platforms), and are attractive to domestic and foreign investors. The purpose of this study is to evaluate, analyze, and measure the influence of financial and human resources on the business performance of commercial enterprises in Hanoi City to propose some recommendations to help commercial enterprises in Hanoi City improve business performance and expand scale. Methodology via a survey was conducted with the participation of employees of commercial enterprises in Hanoi City, including the board of directors, accounting department and sales department. However, only 285 survey forms met the requirements and were processed. Analytical methods such as descriptive statistics, the Cronbach alpha coefficient analysis, EFA analysis, correlation analysis and the regression model are used to test and measure the scales. Research results show that financial resources and human resources have a positive influence on the business performance of commercial enterprises in Hanoi City. This research uses the contents of the financial resources and human resources of firms and the business performance of firms based on prior studies in the realm of firms. Within the context of digital technology, these variables are useful solutions for firms.